PERSEPSI MAHASISWA TENTANG IMPLEMENTASI UNDANG-UNDANG NOMOR 9 TAHUN 1998 TENTANG KEMERDEKAAN MENGEMUKAKAN PENDAPAT DIMUKA UMUM DI UNIVERSITAS RIAU PEKANBARU - ', Riyati; ', Hambali; ', Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by the rise of the action to express opinions in public that disrupt public order by being anarchists. Whereas in expressing opinions in public has no laws that govern namely Law No. 9 of 1998 concerning Freedom Prepaid Suggests Public Opinion. Students as intellectuals active in monitoring the running of the government, so in berpersepsi they will be more critical academic. The purpose of this study was to determine students' perceptions on the implementation of Law No. 9 of 1998 concerning Freedom Prepaid Suggests Public Opinion. This research was conducted at the university riau pekanbaru. Samples of this study was 180 respondents, 20 respondents representing each of the faculties with a total of 9 faculties. Using quota sampling technique. Data from this study were obtained from questionnaires, observation, and documentation. Mechanical if the data were analyzed descriptively, in processing the data obtained from a questionnaire distributed to respondents is presented in the form of a percentage, using the formula P = F / N x 100%. Based on the writer's observation field that students' perceptions on the implementation of Law No. 9 of 1998 on freedom of expression in public is